Analisis Ekspor Karet Provinsi Jambi ke India pada Periode Tsunami Covid-19 - Oeliestina Oeliestina (Universitas Batanghari Jambi, 2022)
The economy of Jambi Province is supported by the agricultural sector with a contribution to the Gross Regional Domestic Product (GRDP) reaching 30.85 percent. The most dominant sub-sector is an annual plantation with palm oil and rubber as the main commodities. Nationally, the rubber plantation area of Jambi Province is in third place after the provinces of South Sumatra and North Sumatra. Rubber is a source of livelihood for the people of Jambi and a source of foreign exchange because rubber is the prima donna of Jambi Province exports. One of the rubber export destinations for Jambi Province in India. The Covid-19 tsunami that hit India in March-June 2021 is expected to affect Jambi Province's rubber exports. An analysis will be carried out on the development of Jambi Province's rubber exports during the Covid-19 tsunami period and see the effect of the Covid-19 tsunami in India on Jambi Province's rubber exports. This study uses descriptive analysis, normality test, and independent sample t-test to see the effect of the Covid-19 tsunami on rubber exports to India. The results of the Kolmogorov Smirnov normality test reached a significance of 0.200. Meanwhile, the normality test with Shapiro Wilk stated a significance of 0.720 before the Covid-19 tsunami and 0.161 during the Covid-19 tsunami. This means that Jambi Province's export data is normal because the significance is > 0.05. The results of the independent sample T-test on export data show that the Covid-19 tsunami did not affect Jambi Province's export activities to India. This can be observed from the significance value at equal variances assumed of 0.482 (> 0.05). This means that rubber exports to India will continue despite extraordinary events such as the COVID-19 tsunami.